Recruiting Agencies - As a Modern Instrument for Employment - S.A.Bozorova. (Zien Journals, 2022)
The article shows that recruitment agencies are a new intermediary in the labor market infrastructure. As a result of the study, the priorities of recruitment agencies in Uzbekistan in providing employment are identified.
Keywords: Recruitment agencies; recruitment; employment of the population; outsourcing